PENGARUH MEDIA KOMIK DIGITAL BERBASIS PLATFORM INSTAGRAM TERHADAP MINAT DAN HASIL BELAJAR IPA SISWA KELAS VIII DI SMP NEGERI 4 TARAKAN - Larasaty Dwiyanty Pratiwi; Vlorensius Vlorensius; Nur Fitriana Sam (Biopedagogia, 2023)
The study aims to determine the effect of digital comic intagram media on students’ learning interest and science learning achievement of eight graders at SMP Negeri 4 Tarakan. This research was quantitative research with a quasi-experimental research method. Research data collection used pretest-posttest and questionnaires. Purposive sampling was aplplied to take the research sampel, and the sampel was eighth graders. The research result showed thet the experimental class possessed a learning interest mean score of 45% higher rhan the control class, where the control class achieved 58.5%. feeling happy got 89% for experimental and 55% for control. The involment aspect was 30% lower than the experimental with 79%. The interest aspect still was led by experimental at 83%, and control only gained 59%. Paying attention aspect was driven by experimental about 49% where the control was only at 59%. Furthermore, the learning achievement results stated that the experimental class was better than the control class, where the test value was 12,329 at a significance level of 0.05, and df 60 is a ttable value of 2.000. this reserch result claimed that digital comic Instagram media totally influenced the studets’ learning interest and achievement in scince class.